2009
DOI: 10.1136/jcp.2009.070961
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological activation of the p53 pathway in haematological malignancies

Abstract: p53 gene mutations are rarely detected at diagnosis in common haematological cancers such as multiple myeloma (MM), acute myeloid leukaemia (AML), chronic lymphocytic leukaemia (CLL) and Hodgkin's disease (HD), although their prevalence may increase with progression to more aggressive or advanced stages. Therapeutic induction of p53 might therefore be particularly suitable for the treatment of haematological malignancies. Some of the anti-tumour activity of current chemotherapeutics has been derived from activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 83 publications
(83 reference statements)
1
40
0
Order By: Relevance
“…16 Monoallelic deletion of TP53 in MM, which often occurs without mutation to the other allele, is associated with an extremely poor prognosis. 17 This supports the idea that a decrease in TP53 levels is associated with tumor progression and numerous reports have shown that therapeutic induction of TP53 might be particularly suitable for the treatment of hematological malignancies, 18 including MM. 19,20 Recent research shows that alteration of miRNA expression during progression from monoclonal gammopathy of undetermined significance (MGUS) to newly diagnosed MM could be partially responsible for TP53 inactivation in MM patients.…”
Section: Discussionsupporting
confidence: 67%
“…16 Monoallelic deletion of TP53 in MM, which often occurs without mutation to the other allele, is associated with an extremely poor prognosis. 17 This supports the idea that a decrease in TP53 levels is associated with tumor progression and numerous reports have shown that therapeutic induction of TP53 might be particularly suitable for the treatment of hematological malignancies, 18 including MM. 19,20 Recent research shows that alteration of miRNA expression during progression from monoclonal gammopathy of undetermined significance (MGUS) to newly diagnosed MM could be partially responsible for TP53 inactivation in MM patients.…”
Section: Discussionsupporting
confidence: 67%
“…28 The mechanism for such resistance to apoptosis has been linked to the overexpression of MDM2 and to inactivation of p53. 29 Thus, drugs targeting inhibition of proteasome-mediated degradation of p53 has emerged as a vital research area in the search for novel therapeutic approaches. Hideshima et al first showed that velcade acts directly to inhibit the growth of MM cell lines and patient samples, assessed by MTT assay and DNA synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…MDM2 is the principal endogenous negative regulator of p53 and is an E3 ligase, which binds to the amino terminal p53 and facilitates proteasomal degradation of p53 (11,12). Due to the importance of the p53-MDM2 interaction, pharmacologic activation of the p53 pathway by inhibition of MDM2 binding has been shown to be an alternative therapeutic strategy in various cancers, including hematologic malignancies (13,14).…”
Section: Introductionmentioning
confidence: 99%